A Happy Congolese Sisyphus? Rolling the Rock of the Conradian Project AD Vitam Eternum! (Global Journal of Human-Social Science, 2015)
This paper shows that the major problem of the Congo is to move from an extractive space to a political one, that is to say, resolutely abandon the Leopoldian and colonial state model. This is the challenge facing the Congolese since independence, but it has its roots in the original strategy of political and economic organization of the Congo Basin. The magnitude of this titanic challenge was clear from the accession of the Congo to independence and to this day Leopoldian model is still very present. Getting rid of it is the task many generations of Congolese have to reckon with.